USE OF SPRAYING DEVICES IN PLANT PROTECTION - Sattorov Shokhimardon Khushmamatovich; Usmonov Muhriddin Mukhtor o‘gli; Abdillayev Marat Ibodillayevich; Kimsanboyev Khujamurat Khamrokulovich; Alamuratov Raimjon Abdimurat Ugli (Web of Journals Publishing, 2025)
The article provides information on the description, classification, use in chemical treatment against harmful organisms, as well as ensuring the safety of sprayers used in agriculture in the Republic of Uzbekistan for the environment and humans.
Keywords: Agriculture, plants, pests, diseases, weeds, spraying equipment, chemical treatment